Measuring program quality using sensors: Childcare professional's experience, perceptions, and needs - Dawn L. Davis; Danae Dinkel; Priyanka Chaudhary; Abbie Raikes (Global Pediatrics, 2024)
High quality early childhood education programs can positively impact children's development. A growing body of research has used technology to measure aspects of quality in childcare environments, including sensors to measure the indoor built environment (temperature, light, and noise), physical activity in children and caregivers, and language environments. However, while sensors may generate significant research insights into childcare quality, little work has explored the acceptability of sensors for wide scale use in childcare quality improvement efforts. This study explored childcare staff's experiences with and perceptions of different sensors that could be used to measure parameters of quality indicators in early childcare programs. Research questions were addressed by applying a mixed methods approach using the Unified Theory of Acceptance and Use of Technology framework. Data was collected through online surveys and interviews. Results indicate that childcare staff have little experience with sensors, but most would be comfortable with sensor use in their programs and about half were interested in using them to measure various aspects of quality of childcare environments. Privacy and security issues such as data storage and use were raised as critical to address prior to implementation, along with clear communication with parents and childcare professionals on reasons for using sensors and the documentation of the value of sensor data in predicting child development. The findings highlight the need to include childcare staff and parents in the design of sensor systems and to consider how information will be shared and used.